The Role of Al-Qur'an Learning Center for Children in Increasing of Religious Moderation Values in Kenagarian Air Bangis, West Pasaman - Asmara, Musda; Kurniawan, Rahadian; Sarweni, Sarweni; Wijayanti, Fian (JURNAL AT-TURAS, 2023)
Kenagarian Air Bangis is located in West Pasaman Regency, West Sumatra Province, one of the heterogeneous areas in Minangkabau. Therefore, it is important to instill and teach the values of religious moderation to students from an early age so that it is easy to appreciate and respect other people of different ethnicities, races, and religions. This study aimed to see whether the understanding of religious moderation has been instilled in students. The study results concluded that the Al-Qur'an Learning Center For Children (TPA) in Kenagarian Air Bangis had shown its role as a non-formal educational institution in instilling and implementing religious moderation values in students. Teachers on faith, morals, and adab have delivered teaching materials related to religious moderation. Even though it has not been structured and managed properly, the values contained in national commitment, tolerance, anti-radicalism and violence, and accommodating local culture have been conveyed to students, such as respecting followers of other religions and respecting people of different ethnicities, races, and religions. It is proven that they have never received discriminatory treatment, harassment, and inter-religious bullying in the Kenagarian Air Bangis; they live side by side even though the non-Muslim community is far from the Muslim community, but in social relations and service to the community, they are treated the same as their rights as a citizen.